Spectrum Cartography using quantized observations - Daniel Romero; Seung-Jun Kim; R. López-Valcarce; Georgios Giannakis (IEEE Int. Conference on Acoustics, Speech and Signal Processing (ICASSP), 2015)
This work proposes a spectrum cartography algorithm used for learning the power spectrum distribution over a wide frequency band across a given geographic area. Motivated by low-complexity sensing hardware and stringent communication constraints, compressed and quantized measurements are considered. Setting out from a nonparametric regression framework, it is shown that a sensible approach leads to a support vector machine formulation. The simulated tests verify that accurate spectrum maps can be constructed using a simple sensing architecture with significant savings in the feedback.
Keywords: cognitive radio; compass; compressed sensing; spectrum sensing